Pet Grief: When is Non-Human Life Grievable?. (February 2015) - Redmalm, David
This study explores how pet owners grieve their pets and view their pets' transience. Drawing on Butler's notion of the differential allocation of grievability, I have analysed interviews with eighteen pet owners. Butler argues that grievability is made possible by a normative framework which allows for some human or humanlike lives to be grieved, while other lives are rendered 'lose-able'. All the interviewed pet owners say that they are capable of grieving a non-human animal, but analysis suggests that they make their pets grievable and ungrievable by turns. I argue that by maintaining this ambivalence, the interviewees negotiate pets' inclusion in a human moral community while simultaneously defending human exceptionalism. The article concludes with a discussion of pet grief as a potentially destabilizing emotion. I suggest that grieving beings on the border between grievable human and lose-able animal – 'werewolves' according to Giorgio Agamben – may be a powerful way of challenging normative frameworks which arbitrarily render some human and non-human lives lose-able.